Self-assembled ordered structures in thin films of HAT5 discotic liquid crystal - Morales, Piero; Lagerwall, Jan; Vacca, Paolo; Laschat, Sabine; Scalia, Giusy (Beilstein Journal of Organic Chemistry, 2010)
Thin films of the discotic liquid crystal hexapentyloxytriphenylene (HAT5), prepared from solution via casting or spin-coating, were investigated by atomic force microscopy and polarizing optical microscopy, revealing large-scale ordered structures substantially different from those typically observed in standard samples of the same material. Thin and very long fibrils of planar-aligned liquid crystal were found, possibly formed as a result of an intermediate lyotropic nematic state arising during the solvent evaporation process. Moreover, in sufficiently thin films the crystallization seems to be suppressed, extending the uniform order of the liquid crystal phase down to room temperature. This should be compared to the bulk situation, where the same material crystallizes into a polymorphic structure at 68 °C.
Keywords: AFM; discotic liquid crystals; hexapentyloxytriphenylene; self-organization; thin films

(untitled) - Laschat, S.; Baro, A.; Giesselmann, F.; Haegele, C.; Scalia, G.; Steinke, N.; Judele, R.; Tosoni, M.; Kapatsina, E.; Schreivogel, A.; Sauer, S. (Angew. Chem., Int. Ed., 2007)

(untitled) - Sergeyev, S.; Pisula, W.; Geerts, Y. H. (Chem. Soc. Rev., 2007)

(untitled) - Pisula, W.; Menon, A.; Stepputat, M.; Lieberwirth, I.; Kolb, U.; Tracz, A.; Sirringhaus, H.; Pakula, T.; Muellen, K. (Adv. Mater., 2005)

(untitled) - Christ, T.; Glusen, B.; Greiner, A.; Kettner, A.; Sander, R.; Stumpflen, V.; Tsukruk, V.; Wendorff, J. H. (Adv. Mater., 1997)

(untitled) - Schmidt-Mende, L.; Fechtenkotter, L.; Mullen, K.; Moons, E.; Friend, R. H.; Mackenzie, J. D. (Science, 2001)

(untitled) - Hassheider, T.; Benning, S. A.; Lauhof, M. W.; Kitzerow, H. S.; Bock, H.; Watson, M. D.; Mullen, K. (Mol. Cryst. Liq. Cryst., 2004)

(untitled) - Simpson, C.; Wu, J.; Watson, M. D.; Mullen, K. (J. Mater. Chem., 2004)

(untitled) - Zimmermann, S.; Wendorff, J. H.; Weder, C. (Chem. Mater., 2002)

(untitled) - Van de Craats, A. M.; Stutzmann, N.; Bunk, O.; Nielsen, M. M.; Watson, M.; Muellen, K.; Chanzy, H. D.; Sirringhaus, H.; Friend, R. H. (Adv. Mater., 2003)

(untitled) - Henderson, P.; Beyer, D.; Jonas, U.; Karthaus, O.; Ringsdorf, H.; Heiney, P. A.; Maliszewskyj, N. C.; Ghosh, S. S.; Mindyuk, O. Y.; Josefowics, J. Y. (J. Am. Chem. Soc., 1997)

(untitled) - Tracz, A.; Jeszka, J. K.; Watson, M. D.; Pisula, W.; Muellen, K.; Pakula, T. (J. Am. Chem. Soc., 2003)

(untitled) - Lee, J.-H.; Kim, H.-S.; Pate, B. D.; Choi, S.-M. (Physica B, 2006)

(untitled) - Adam, D.; Closs, F.; Frey, T.; Funhoff, D.; Haarer, D.; Ringsdorf, H.; Schuhmacher, P.; Siemensmeyer, K. (Phys. Rev. Lett., 1993)

(untitled) - Lagerwall, J.; McCann, J. T.; Formo, E.; Scalia, G.; Xia, Y. (Chem. Commun., 2008)

(untitled) - Grelet, E.; Bock, H. (EPL, 2006)

(untitled) - Krüerke, D.; Rudquist, P.; Lagerwall, S. T.; Sawade, H.; Heppke, G. (Ferroelectrics, 2000)

(untitled) - Usol′tseva, N.; Hauck, G.; Koswig, H. D.; Praefcke, K.; Heinrich, B. (Liq. Cryst., 1996)

(untitled) - Palmans, A. R. A.; Vekemans, J. A. J. M.; Hikmet, R. A.; Fischer, H.; Meijer, E. W. (Adv. Mater., 1998)

(untitled) - Duzhko, V.; Shi, H. F.; Singer, K. D.; Semyonov, A. N.; Twieg, R. J. (Langmuir, 2006)